Sacco e Vanzetti: il cinema di Giuliano Montaldo tra autorialità e genere - Bilchi, Nicolas; Bilchi, Nicolas (Scenari, 2021)
The article intends to suggest a possible reading of Giuliano Montaldo’s cinema, starting from a stylistic analysis of the film Sacco e Vanzetti (1971). It will be highlighted the interweaving of expressive solutions related to film genres with personal and “authorial” linguistic choices, aimed at ensuring the immediate understanding of the film’s political content for the general public, as well as offering mostly stratified layers of meaning for the a more aware and attentive viewer.